Pengaruh Kualitas Produk, Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Konsumen Pengguna TikTok Shop (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to analyze the influence of Product Quality, Service Quality, and Price Perception on Consumer Satisfaction on TikTok Shop users partially and simultaneously. Including quantitative studies, this study applies the Lameshow and purposive formulas to determine the sample, namely 100 respondents of students of the Faculty of Economics, University of 17 August 1945 Surabaya, TikTok Shop users in Surabaya. The results of the analysis using SPSS show that Product Quality, Service Quality, and Price Perception affect Consumer Satisfaction partially, positively and significantly. The three variables also affect Consumer Satisfaction positively, significantly and simultaneously.